A study on financial statement analysis of NXP Semiconductor during global economy crisis for the year 2008 / Nur Harmizan Mohd Zaki - Mohd Zaki, Nur Harmizan (2012)
The performance of the company can be measured by the fundamental analysis and technical analysis. Financial statement analysis is one of the techniques in fundamental analysis. Financial statement analysis is the process of understanding the risk and profitability of a firm through analysis of reported financial information, particularly annual and quarterly reports. This study was conducted in Finance Department of NXP Semiconductors. The objectives of this study are to identify the factor that affects the company performance and to analyze the trend of financial statement of the company for the year 2005 to 2009. For the purpose of this study, three financial statement analysis tools will be used which is comparative analysis, common size analysis and ratio analysis. Data for this study are gathered from primary and secondary data. This study shows this company has low performance in five consequences years (2005-2009). Even NXP unable to manage their capital structure and solvency ratio during these five years, but it has strength in their credit analysis. This financial statement analysis are reliable to be use in analyzing the financial performance and trend for company.